Preparation and modification of alkaline bricks by using industrial residues and calcium stearate. Issue 1 (28th July 2016) - Liu, Chenxu; Liu, Bo; Chen, Xidong; Zhang, Jin; Duan, Wubiao; Guo, Jianping; Han, Junping; Zhang, Yanxian; Yu, Shuxuan; Hu, Kunsheng
Abstract : New environmentally friendly alkaline bricks were produced with the utilization of industrial residues (alkaline residue and fly ash) as main resources and novel combination of calcium stearate as an addition. By adjusting the ratio of alkaline residue and fly ash, reducing the water cement ratio, the flexural and compressive strengths of the alkaline bricks reached up to 2.5 MPa and 10 MPa, which has reached the corresponding Chinese Testing Standards. Moreover, by adding a small amount of calcium stearate (0.50%, wt), the concentration of extracted chloride ion was decreased by 30% and the resistance to freezing was doubled, which the bricks can be possibly used in the Northern China. In addition, the micro‐modification mechanism was provided and the practical application was analyzed. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 21–26, 2017